Freins et leviers de l’adaptation au changement climatique : représentations des acteurs de moyenne montagne - Lutoff Céline; Arina Susa; Stéphane La Branche; Chloé Maréchal; Aurélie Chamaret (VertigO)
In the context of climate change, authorities must take actions for adapting to local impacts. However, one can notice that they have difficulties doing so. In this study, we aim at identifying the obstacles to action, or on the contrary, what can be levers for adaptation. We investigated mid altitude mountains at mid latitudes in the French Alps (western Europe), where the impacts of climate change are already clear. A double survey has been realized with authorities over the French region Auvergne Rhône-Alpes, for observing their perception of levers and obstacles for adaptation at local scale. Nuancing literature, the results states that the failure to bring action at local scale is not necessarily due to a weak awareness of climate change impacts, but rather to uncertainties in i) possible futures of climate and territories, ii) knowledge brokering on global changes and their local impacts and iii) relevance of actions undertaken. Interviewees, local actors directly involved into the definition of adaptation strategies, reveal a need of places for dialogue and sharing of experiences on adaptation, but also a need for guidance to initiate major changes toward reducing vulnerabilities of mid altitude mountains.